The Impact of Changes in Cloud Water pH on Aerosol Radiative Forcing. Issue 7 (9th April 2019) - Turnock, S. T.; Mann, G. W.; Woodhouse, M. T.; Dalvi, M.; O'Connor, F. M.; Carslaw, K. S.; Spracklen, D. V.
Abstract: Oxidation of sulfur dioxide (SO2 ) in cloud water by reaction with ozone is an important sulfate aerosol formation mechanism and strongly dependent on the acidity of cloud water. Decadal reductions in Northern Hemisphere sulfur emissions have contributed to higher cloud water pH, thereby altering sulfate formation rates. Here we use a global composition‐climate model to show that changes in cloud water pH over the 1970–2009 period strongly affects the aerosol particle size distribution, cloud condensation nuclei concentrations, and the magnitude of aerosol radiative forcing. The simulated all‐sky aerosol radiative forcing (1970–2009) over the North Atlantic is +1.2 W m −2 if pH remains constant at 5.0, as in many climate models. However, the forcing increases to +5.2 W m −2 if pH is assumed to increase by 1.0 unit over this period. Global composition climate models need to account for variations in cloud water pH to improve the representation of sulfate aerosol formation and aerosol radiative effects. Plain Language Summary: Particles in the atmosphere (aerosols) can be harmful to human health at the surface and also affect the Earth's climate. Sulfate is a major component of atmospheric aerosols. It is formed from chemical reactions involving sulfur dioxide, which has large man‐made sources in the energy and industrial sectors. This study investigates the sensitivity of sulfate aerosol formation in clouds to the assumed acidity of the cloud water. Large changes in man‐made emissions over the Northern Hemisphere in the last 30 years have altered the acidity of cloud water. Here we used climate model simulations that include a representation of aerosols and chemistry to investigate the effect of changes in cloud water acidity on sulfate aerosol formation between 1970 and 2009. Our analysis shows that changes in the acidity of cloud water has a strong effect on the properties of aerosols and how they interact with the Earth's radiative balance. The impact is shown to be particularly important for cloudy regions like the North Atlantic that are sensitive to changes in aerosols. The results highlight that the impact of changes in cloud water acidity on aerosols should be included within climate models to improve our representation of aerosols and their interaction with climate. Key Points: Increases in assumed cloud water pH can improve simulation of sulfate aerosols Aerosol radiative forcing over the last 40 years is sensitive to the value of cloud water pH Global composition climate models assuming a fixed value of cloud water pH do not fully account for recent aerosol radiative forcing